Pengaruh Aromaterapi Mawar terhadap Intensitas Nyeri Persalinan Kala I Fase Aktif di PMB Wilayah Kerja Puskesmas Pardasuka - Komalasari Komalasari; Desti Mayasari; Yona Desni Sagita; Eka Tri Wulandari (JUKEJ : Jurnal Kesehatan Jompa, 2026)
Untreated labor pain can increase catecholamine secretion, leading to vasoconstriction, decreased uterine contractions, and a higher risk of complications. Various non-pharmacological methods have been used to reduce pain, one of which is aromatherapy. Rose aromatherapy provides a relaxing effect and reduces pain perception. This study aimed to determine the effect of rose aromatherapy on the intensity of labor pain during the active phase of the first stage of labor. A quasi-experimental design with a posttest-only control group design was used. The study involved 30 laboring women divided into two groups, with 15 respondents in each group. The intervention group received rose aromatherapy by diffusing 3–5 drops of essential oil mixed with 100 ml of water for 15 minutes, while the control group received standard normal labor care. Pain intensity was measured using the Numerical Rating Scale (NRS) and analyzed using the Mann–Whitney test. The results showed that the average pain intensity in the control group was 7.40 (60%), while in the intervention group it was 5.33 (46.7%), indicating a 13.3% reduction in pain level with a p-value of 0.000 < 0.05. This indicates a significant effect of rose aromatherapy on the intensity of labor pain during the active phase of the first stage of labor at the midwifery private practice (PMB) in the working area of Pardasuka Community Health Center in 2025. Based on these findings, it can be concluded that rose aromatherapy is effective in reducing labor pain intensity during the active phase of the first stage of labor. Keyword : Rose Aromatherapy, Labor Pain, First Stage Active Phase, Pain Management